Penerepan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas VI Sekolah Dasar - Prastiwi, Danik; Istriyanti, Sri Fajar; Sutoro, Meiria Wulandari; Sudigdo4, Anang; Santosa, Wijaya Heru (Universitas Negeri Makassar, 2024)
This research was designed with the aim of assessing the impact of implementing the Problem Based Learning (PBL) learning model on the achievement of Indonesian language learning for Class VI students at Karangrejo 3 Elementary School, Selomerto District, Wonosobo Regency. This type of research is Classroom Action Research (CAR) which adopts the spiral model from C. Kemmis and Mc. Taggart, with implementation in 2 cycles. Each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The data analysis technique in this research uses quantitative descriptive analysis techniques obtained from primary data during the research. The research results showed an increase in the level of completion of Indonesian cognitive learning outcomes scores, as measured by KKM ≥ 75, between pre-cycle, cycle 1 and cycle 2, amounting to 42.10%: 73.68%: 84.21%. From the findings of this research, it can be concluded that the application of problem-based learning has been proven to be able to increase the learning outcomes of Class VI students at SD 3 Karangrejo, Selomerto District in Indonesian language subjects, especially in the odd semester of the 2022/2023 academic year.